Management of broken instrument by file bypass technique - Parveen, Sultana; Hossain, Mozammal; Uddin, Md. Farid (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Different devices and techniques have been developed to retrieve fractured instruments during the endodontic procedures. This case report describes the management of a broken instrument, which was accidentally broken during cleaning and shaping of the root canal in right 2nd molar tooth. A # 25 stainless steel K-file was separated in mesiobuccal canal of the treated tooth. At first, a radiograph was taken to confirm the level of separation of the instrument. The instrument was found to be separated at the apical 3rd of the mesial canal and then file bypass technique was performed. Calcium hydroxide dressing was given for 7 days followed by obturation with guttapercha cone and zinc oxide eugenol sealer in lateral condensation technique. It can be concluded that bypass technique can be considered as simple and effective technique for the management of broken instrument into the root canal.